GE_GERICHTE C/15019/2011 vom 10. Juni 2015 - GE Cour de justice (2015)
ACTION EN RESPONSABILITÉ; LIEN DE CAUSALITÉ; EXPERTISE JURIDIQUE; DOMMAGE MÉNAGER; PREUVE ILLICITE | CPC.187.4; CPC.188.2; CPC.152.2; CO.46.1; CO.44.1